what number is the simplified expression equal to, 13 - 7 + (2 x 5 - 1) divided by 3 + 7.

can someone help me with this???

8 answers

yoo hoo!!!!!!?????
anybody there????
i really need help with this!!
please
never mind i think i figured it out.I got the answer 17.and right now, i think it is correct so adios!!!!
I get 16 , not 17
I get 12, not 17.

you have to do the order of operations first, everything in parethesis first and multiplication/division must be done before addition/subtraction.

(2x5-1)=9
13-7+9=15
15/3 + 7=
5+7=12
12
Hope this is right and I hope it helped.
13 - 7 + (2 x 5 - 1)/3 + 7
= 6 + (9)/3 + 7
= 6 + 3 + 7
= 16

http://www.google.com/search?hl=en&q=13+-+7+%2B+%282*5+-+1%29%2F3+%2B+7&oq=13+-+7+%2B+%282*5+-+1%29%2F3+%2B+7&aq=f&aqi=h1&aql=&gs_sm=3&gs_upl=78965l104593l0l109667l20l20l0l0l0l0l134l1778l17.3l20l0